Trends in telecommunication systems for drivers. (4th August 2014) - Okada, Yashuhiro
Significant improvements are continually being achieved in the information and communications equipment used in vehicles today. The driving forces behind this progress are the vigorous R&D activities of car makers and equipment manufacturers, and the experimental system projects being promoted by governmental agencies. Automotive telecommunications systems make use of radio waves, which represent a limited resource, and these have the potential to affect greatly road traffic conditions and the safety of vehicle occupants. For these reasons, the implementation and operation of these systems is an issue that requires a social consensus and close co–ordination with governmental authorities. This paper examines the need for automotive telecommunications systems as seen from the viewpoint of the vehicle occupants, and surveys the development work being undertaken today. It also poses several problematic issues concerning these systems and discusses the future potential of vehicle information and communications systems.